2014
DOI: 10.1530/eje-14-0375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pain in patients with pituitary adenomas

Abstract: Objective: Clinical presentation of pituitary adenomas frequently involves pain, particularly headache, due to structural and functional properties of the tumour. Our aim was to investigate the clinical characteristics of pain in a large cohort of patients with pituitary disease. Design: In a cross-sectional study, we assessed 278 patients with pituitary disease (nZ81 acromegaly; nZ45 Cushing's disease; nZ92 prolactinoma; nZ60 non-functioning pituitary adenoma). Methods: Pain was studied using validated questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
(35 reference statements)
8
17
1
Order By: Relevance
“…The exception, however, were the 3 patients in whom severe headache persisted, since their QoL did not improve, independently of their hormonal values after therapy [18]. In a further recent study, the presence of headache was also correlated with worse QoL but not with depression in acromegaly, while neuropathic pain determined both impaired QoL and depression [19]. …”
Section: Health-related Qol In Acromegalymentioning
confidence: 99%
“…The exception, however, were the 3 patients in whom severe headache persisted, since their QoL did not improve, independently of their hormonal values after therapy [18]. In a further recent study, the presence of headache was also correlated with worse QoL but not with depression in acromegaly, while neuropathic pain determined both impaired QoL and depression [19]. …”
Section: Health-related Qol In Acromegalymentioning
confidence: 99%
“…Our research group has assessed 80 patients with CD in a cross-sectional setting. Results indicate that, in a cross-sectional observational study, patients with CD were shown to have a particularly high susceptibility to pain 21 and increased anxiety-associated personality traits. 22 This study will expand on these previous findings.…”
Section: Discussionmentioning
confidence: 91%
“…We recorded a high prevalence of bodily pain (65%) and headache (64%); adrenocorticotropic adenomas were most frequently associated with pain (76%). Headache was equally frequent in patients with macro-and microadenomas (P = 0.266), while the majority of patients suffered from nociceptive pain (80%) (16).…”
Section: Somatic and Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
“…The significant impact of chronic exposure to hypercortisolism on patient's health and healthrelated quality of life (HRQoL) has been demonstrated with generic questionnaires (17). The presence of pain and pain-related disability correlates significantly with impaired QoL in CD (16). All HRQoL parameters improve after treatment with TSS, however, even after long-term remission of CS, impaired QoL persists as a remaining effect of long-standing hypercortisolism, especially in the presence of hypopituitarism (18).…”
Section: Quality Of Life (Qol)mentioning
confidence: 99%
See 1 more Smart Citation